T-lymphocyte subsets (CD4/CD8 ratio) in breast cancer patients - Sevcíková, L; Hunáková, L; Chorváth, B; Turzová, M; Boljesíková, E (Neoplasma, 1992)
T-lymphocyte subsets (CD4/CD8 antigen positive cells) were determined in peripheral lymphocytes from 48 patients with breast cancer of different stages by flow immunocytometry with the aid of anti-CD4 and CD8 monoclonal antibodies. A broad individual variability of the CD4/CD8 ratio among both healthy donors and breast cancer patients was observed. The average value of CD4/CD8 ratio decreased in groups as follows: Healthy donors and Stage I patients, Stage IIA, IIB and Stage IV breast cancer patients. These differences were generally statistically not significant. The difference between healthy donors and Stage IV breast cancer patients was statistically significant (p < 0.01), if one exceedingly elevated value of the CD4/CD8 ratio was excluded from statistical evaluation. The average CD4/CD8 value in the group of breast cancer patients with lymph node or distant metastases was lower than that of patients without metastases, but their difference was not statistically significant either.
Keywords: CD4-CD8 Ratio; nádory prsu; T-Lymphocyte Subsets; Female; poměr CD4 a CD8 lymfocytů; Neoplasm Staging; Breast Neoplasms; staging nádorů; Humans; ženské pohlaví; lidé; T-lymfocyty - podskupiny